Effect of the inclusion of silage of trout residues in pigs feed and its effect on the productive performance and the taste of meat - Calderón-Quispe, Víctor (2017)
The study aimed to determine the effect of the level of inclusion of silage from trout residues (ERT) in concentrate feed on body weight, feed intake, feed conversion of pigs and taste of pig meat. Three treatments were applied: a control (T1, 0%) and two treated groups with 5% (T2) and 10% (T3) of ERT in the ration, with five replicates per treatment. Thirty non-castrated male pigs (York-Duroc-Landrace) of 45 days of age were used. Feeds for the growing and finishing phase were formulated to be similar in protein (CP) and energy (ME) content (growing: 16.0% CP and 3.20 Mcal ME/kg and finishing: 13.0% CP and 3.20 Mcal ME/kg) and were administered ad libitum during 98 days. Body weight, feed intake and feed conversion rate were determined at 56 and 98 days. In addition, a sensory test of meat was carried out at the end of the study to evaluate the taste of the meat. The results at day 98 showed no differences between treatments on body weight (69.8, 81.3 and 86.4 kg for T1, T2 and T3 respectively) and feed intake (1.30, 1.50 and 1.54 kg/day for T1, T2 and T3 respectively). However, feed conversion improved when ERT was added to the ration (2.25, 2.15 and 2.04 for T1, T2 and T3 respectively, p=0.012). The sensorial evaluation indicated that ERT inclusion in feed did not affect the taste of the meat. In conclusion, the inclusion up to 10% of ERT in pig feed improves feed conversion and do not affect the taste of meat.